Use of Videoscribe Animation-Based Science E-Modules on Science Literacy of Junior High School Students - Sri Arwini Bahrun Bahrun; Khamsiah Mawar Fatmah; Insih Wilujeng; Suyanta Suyanta; Sri Rejeki (Jurnal Penelitian Pendidikan IPA, 2023)
Scientific literacy must be mastered by students because it relates to the environment. This study aims to determine the increase in students' scientific literacy abilities using videoscribe animation-based e-modules. The type of research used is descriptive quantitative conducted at SMPN 5 Depok, Yogyakarta. The tsubjects in this study were 32 class VII B students who were selected using cluster random sampling. The instrument used in this study was a test in the form of multiple-choice questions with data collection techniques in the form of pretest and posttest questions. Based on the differences in the pretest and posttest results obtained and the average N-gain obtained 0,62, it is in the medium category which indicates that the videoscribe animation-based science e-module used can improve students' scientific literacy skills.